An Overview of Advanced Hyphenated Techniques for Simultaneous Analysis and Characterization of Polymeric Materials. Issue 6 (1st November 2016) - Lin, Shan-Yang
ABSTRACT: Polymers or polymeric materials are almost ubiquitous in our daily lives, and their production involves major industrial efforts worldwide. Smart polymers have been developed for diverse purposes ranging from commodities to high-tech medical applications. In particular, bio-based polymers have attracted increasing attention because of environmental concerns and the realization that global petroleum resources are finite. A great quantity of these polymers has been synthesized, and more will be produced in the future. Therefore, their characterization requires various analytical instruments and methods. This article presents the most comprehensive overview of basic operational principles of various advanced hyphenated techniques for polymer analysis and characterization and to present several literature examples of applications of these techniques. An overview of polymer classification and characterization in terms of physico-chemical, mechanical, thermal, and viscoelastic properties is initially introduced. Next, the polymer characterization by conventional thermal analysis is discussed. Hyphenated analytical technique is online coupling of separation and detection techniques using suitable interfaces. Here, the main focus of this review article will discuss recent advances in the online applications of various hyphenated techniques such as double-, triple-, and quadruple-hyphenated methods along with appropriate examples. This should be the first review article simultaneously introduced and discussed overall above three techniques, rather than only one or two techniques presented in other review article. These hyphenated techniques offer shorter analysis times, increased automation, higher sample throughput, better reproducibility, and reduced contamination. The remarkable improvements observed in these methods are expected to enhance combined selectivity and increase the amount of authentic information obtained. When the hyphenated analytical techniques are combined, however, there will be having synergies and negative consequences. Details on the advantages and disadvantages of the hyphenated coupling techniques should be paid more and more attention on the investigation of polymeric materials.